2013
DOI: 10.1007/s13197-013-1110-z
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Tombul hazelnut (Corylus avellana L.) protein concentrates: functional and rheological properties

Abstract: Turkish Tombul hazelnut consumed as natural or processed forms were evaluated to obtain protein concentrate. Defatted hazelnut flour protein (DHFP) and defatted hazelnut cake protein (DHCP) were produced from defatted hazelnut flour (DHF) and defatted hazelnut cake (DHC), respectively. The functional properties (protein solubility, emulsifying properties, foaming capacity, and colour), and dynamic rheological characteristics of protein concentrates were measured. The protein contents of samples varied in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Ultrasonic application of biopolymer modification has been studied thoroughly. Ultrasound technology, a novel non-thermal technology, is simple, energy saving, cost-effective, and environmentally friendly [7]. Recently, the application of ultrasound technology to improve the efficiency of enzymolysis of protein peptides has been a major focus of research [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic application of biopolymer modification has been studied thoroughly. Ultrasound technology, a novel non-thermal technology, is simple, energy saving, cost-effective, and environmentally friendly [7]. Recently, the application of ultrasound technology to improve the efficiency of enzymolysis of protein peptides has been a major focus of research [5].…”
Section: Introductionmentioning
confidence: 99%
“…The countries, high cost of proteins from animal sources, health problems such as allergies to animal proteins and many consumers choosing freely to refrain consuming animal proteins. This situation has led to a substantial search for alternative sources of proteins which can replace conventional sources more used [15,16]. Alternative sources have been thoroughly studied in recent years with proteins derived from plants (lupin, quinoa, amaranth, and sesame), bacteria, and yeasts being the most promising ones [17].…”
Section: Discussionmentioning
confidence: 99%
“…Hazelnut protein was isolated as Tatar et al reported [ 21 ]. Briefly, DHF dissolved in distilled water was adjusted to a pH of 8.0 with 1% NaOH solution, and stirred for 30 min.…”
Section: Methodsmentioning
confidence: 99%